Dyeing Fabrics with a Colorant Extracted from Blue-Green Algae. Issue 5 (September 2022) - Baek, Na-won; Zhang, Xun; Lou, Jiang-fei; Fan, Xue-rong
Blue-green algae is an environmental problem; they reproduce rapidly and threaten aquatic ecosystems. Therefore, research on their use as a new energy resource is being actively conducted in various fields. This study was carried out to apply the natural dye from blue-green algae to the textile dyeing industry. Two methods were used to dye cotton and silk fabrics using blue phycocyanin dye extracted from blue-green algae. Six mordants were also tested in the process. The dyed fabrics were evaluated through dyeing depth and color fastness (washing, rubbing, dry cleaning, and light) tests. Phycocyanin dyed both fabrics blue and the dyeing effect was better on silk than on cotton fabric. In addition, Al, Sn, and Fe mordants were most effective for dyeing fabrics and co-mordants were more effective than pre-mordants.